2021
DOI: 10.1016/j.jaad.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric allergic contact dermatitis. Part I: Clinical features and common contact allergens in children

Abstract: Allergic contact dermatitis (ACD), a delayed hypersensitivity skin reaction to environmental allergens, has a prevalence that is similar in children and adults. However, diagnostic testing for ACD in pediatric populations accounts for less than one tenth of all patch tests. The relative infrequency of pediatric patch testing may be attributed to the difficulty in testing in this population, which includes a smaller surface area for patch test placement and maintaining cooperation during patch testing, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 135 publications
3
28
0
4
Order By: Relevance
“…The most frequent primary locations of ACD in our study group were roughly those body areas generally clinically suspected of ACD in children. 21 By contrast, it has already been shown that primary dermatitis sites in them cannot predict the diagnosis of ACD, 22 therefore any child with persistent or atypical eczema should be referred for patch testing regardless of the affected primary locations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequent primary locations of ACD in our study group were roughly those body areas generally clinically suspected of ACD in children. 21 By contrast, it has already been shown that primary dermatitis sites in them cannot predict the diagnosis of ACD, 22 therefore any child with persistent or atypical eczema should be referred for patch testing regardless of the affected primary locations.…”
Section: Discussionmentioning
confidence: 99%
“…The ten most frequent contact allergens observed in our population (Table 2) are consistent with the literature in this regard, being metals, fragrances, PPD, ingredients of topical pharmaceutical products and cosmetics, and Compositae plants. 12 Nickel sulfate is the most frequently reported allergen in children worldwide, 21 despite the EU Nickel Directive since 2001, 23 possibly because of nickel-containing toys imported from non-European countries that do not have to comply with these restrictions. 12 wipes), essential oils, diffusers, scented candles, and incense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unusual cases included systemic contact dermatitis from chromium in breastmilk due to excessive consumption of chocolate by the mother 53 and facial dermatitis after being kissed by a grandfather who had gargled mercurochrome mouthwash 54 . Despite the significant burden of ACD in this population, patch testing is underperformed in pediatric patients 55 ; this may contribute to a delayed diagnosis of CACD in children compared with adult patients.…”
Section: Discussionmentioning
confidence: 99%